2013
DOI: 10.1002/ange.201307377
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Aryltrifluoromethylation of Activated Alkenes

Abstract: Metallfrei: Die erste metallfreie Aryltrifluormethylierung von aktivierten Alkenen wurde entwickelt. Mit dieser Methode wurden trifluormethylierte Isochinolindione, Spirobicyclen, Oxindole und α‐Aryl‐β‐trifluormethylamide hoch regioselektiv erhalten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(19 citation statements)
references
References 70 publications
(20 reference statements)
1
18
0
Order By: Relevance
“…As shown in Fig. 6 (i.e., 4f – 4j ), N -aroyl-methacrylamide substrates bearing vicinal dialkyl-substituted unsaturated alkene moieties afforded products in good yields and diastereoselectivities as high as 95:5, which are superior to that obtained from a previously reported homogeneous approach 38 . Notably, 3j , bearing a cyclic allyl moiety, which predominantly forms oligomers in the homogeneous case, was readily converted in a diastereocontrolled manner (d.r.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…As shown in Fig. 6 (i.e., 4f – 4j ), N -aroyl-methacrylamide substrates bearing vicinal dialkyl-substituted unsaturated alkene moieties afforded products in good yields and diastereoselectivities as high as 95:5, which are superior to that obtained from a previously reported homogeneous approach 38 . Notably, 3j , bearing a cyclic allyl moiety, which predominantly forms oligomers in the homogeneous case, was readily converted in a diastereocontrolled manner (d.r.…”
Section: Resultsmentioning
confidence: 65%
“…Unless otherwise stated, solvents were dried and distilled prior to use according to standard methods. 1,1′,1″-[Nitrilotris(4,1-phenylenethiene-5,2-diyl)]triethanone, the precursor of H 3 TCTA 40 , and the starting materials 1p 41 , 3a and 3c 42 , 3b , 3d to 3i 43 , and 3j 38 were synthesized according to literature methods. The other substrates were commercially available and used as received.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly,w hen the starting material was substituted by am ethoxyg roup in the para position, dearomatized spirobicyclic compound 6 was obtained in 75 % yield, with only traces of the corresponding isoquinolinedione. [9] Encouraged by these results of intramolecular trifluoromethylthiolation, we next soughttoe xtend this novel methodology to at hree-component reaction, involvingas tyrene derivative 7, 2f as the SCF 3 source, and an aromatic partner 8 as the nucleophile (Scheme 4). The development of such unknown intermolecular reactions remains as ignificant challenge due to: i) ap otential competitionb etween both reactives pecies 7 and 8 during the trifluoromethylthiolation process, leading to SCF 3substituted aromatic side-products 10;i i) the possible side-reaction with saccharin, which is released during the reaction,a ffording unwanteda minotrifluoromethylthiolated compound 11;i ii)undesired elimination reactions, which may produce vinyl-SCF 3 compounds 12.…”
mentioning
confidence: 99%
“…More recently, the same authors revealed that an iodonium ion could function as the catalyst for these types of reactions. [58] Liang and co-workers reported the trifluoromethylation of 1,6-enynes (Scheme 23). [59] This reaction provided carbo-cycles and heterocycles bearing a trifluoroethyl group on a quaternary carbon center and a vinyl ester moiety.…”
Section: Methodsmentioning
confidence: 99%